Fibrin(ogen) in human disease: both friend and foe - Vilar, Rui; Fish, Richard J.; Casini, Alessandro; Neerman-Arbez, Marguerite (Haematologica (Roma), 2020)
Fibrinogen is an abundant protein synthesized in the liver, present in human blood plasma at concentrations ranging from 1.5-4 g/L in healthy individuals with a normal half-life of 3-5 days. With fibrin, produced by thrombin-mediated cleavage, fibrinogen plays important roles in many physiological processes. Indeed, the formation of a stable blood clot, containing polymerized and cross-linked fibrin, is crucial to prevent blood loss and drive wound healing upon vascular injury. A balance between clotting, notably the conversion of fibrinogen to fibrin, and fibrinolysis, the proteolytic degradation of the fibrin mesh, is essential. Disruption of this equilibrium can cause disease in distinct manners. While some pathological conditions are the consequence of altered levels of fibrinogen, others are related to structural properties of the molecule. The source of fibrinogen expression and the localization of fibrin(ogen) protein also have clinical implications. Low levels of fibrinogen expression have been detected in extra-hepatic tissues, including carcinomas, potentially contributing to disease. Fibrin(ogen) deposits at aberrant sites including the central nervous system or kidney, can also be pathological. In this review, we discuss disorders in which fibrinogen and fibrin are implicated, highlighting mechanisms that may contribute to disease.